2021
DOI: 10.3390/ijms22137135
|View full text |Cite
|
Sign up to set email alerts
|

Possible Link between SARS-CoV-2 Infection and Parkinson’s Disease: The Role of Toll-Like Receptor 4

Abstract: Parkinson’s disease (PD) is the most common neurodegenerative motor disorder characterized by selective degeneration of dopaminergic neurons in the substantia nigra pars compacta (SNpc) of the midbrain, depletion of dopamine (DA), and impaired nigrostriatal pathway. The pathological hallmark of PD includes the aggregation and accumulation α-synuclein (α-SYN). Although the precise mechanisms underlying the pathogenesis of PD are still unknown, the activation of toll-like receptors (TLRs), mainly TLR4 and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 179 publications
1
40
0
Order By: Relevance
“…Also, TLR-4 (Asp299Gly) polymorphism has been linked to bacterial pneumonia susceptibility, probably due to weakened first-line defensive mechanisms [17]. Many studies conducted during the COVID-19 pandemic pointed to the importance of TLR-4 in mounting an effective immune response to SARS-CoV-2 [9,[18][19][20][21].…”
Section: N Discussionmentioning
confidence: 99%
“…Also, TLR-4 (Asp299Gly) polymorphism has been linked to bacterial pneumonia susceptibility, probably due to weakened first-line defensive mechanisms [17]. Many studies conducted during the COVID-19 pandemic pointed to the importance of TLR-4 in mounting an effective immune response to SARS-CoV-2 [9,[18][19][20][21].…”
Section: N Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreaks known as the 2019 novel coronavirus disease (COVID-19) pandemic has caused high levels of concern and economic crisis around the world [ 1 ]. Previous studies have supported a link between SARS-CoV-2 infection and Parkinson’s diseases (PD) [ 2 , 3 , 4 , 5 ]. More recently, several cases of patients with COVID-19 who developed parkinsonism and responded to levodopa have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several studies conducted during the COVID-19 pandemic have found that dysregulated TLR-4 signaling may contribute to the initial failure of viral clearance and the development of COVID-19 severe clinical symptoms, namely adult respiratory distress syndrome (ARDS) and lethal respiratory failure. [5][6][7][8][9] Considering the importance of TLR-4 in initiating innate immunity against SARS-CoV-2, it is supposed that genetic heterogeneity in the TLR-4 gene might explain, at least in part, the broad spectrum of COVID-19 manifestations. Therefore, in this study, we assessed two common TLR-4 single nucleotide polymorphisms (SNPs), Asp299Gly and Thr399Ile, in Egyptian patients with COVID-19 and evaluated their frequency concerning disease severity, progression, and cytokine storm.…”
Section: Introductionmentioning
confidence: 99%